ОЛИЙ ТАЪЛИМ МУАССАСАЛАРИ ТАЛАБАЛАРИНИ ИННОВАЦИОН ТАДБИРКОРЛИК ФАОЛИЯТИГА ТАЙЁРЛАШ ТИЗИМИДА ЁНДАШУВЛАР - Аляминов, Х.И. (SCIENCE and SOCIETY, 2023)
The article deals with modern approaches. The use of modern approrchers will give effective results in preparing future specialists for entrepreneurial activity.
Keywords: personality-oriented; aseological; functional; individual; professional-technological; contextual; knowledge; task